Guarantees for Development - Mirabile, Mariana (OECD Publishing, 2013)
This Working Paper presents the results of a Survey on Guarantees for Development carried out in the context of the OECD DAC work to modernise statistics on external development finance post 2015. No comprehensive and internationally comparable data on guarantees for development and the volume of finance mobilised by them exist at present. This Survey aimed to fill this information gap by estimating the volume of private sector flows to developing countries mobilised by guarantee schemes. Guarantees for development purposes have mobilised over USD 15 billion of private sector flows to/in developing countries over the period of study (2009-11). This report analyses the data from the Survey (e.g. by sector and by country), includes a reflection on how the amount mobilised by guarantees can be captured at an international level and comments on the leverage ratio as a measure of efficiency of development finance
Keywords: Development